Corporate tax revenue and foreign direct investment: Potential trade-offs and how to address them - Sabine Laudage (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Corporate tax revenue and Foreign Direct Investment (FDI) are two key development finance sources according to the Addis Ababa Action Agenda for Financing for Development. These sources are important for developing countries to finance public goods and mobilize private investment for sustainable development. However, certain tax policies can have ambiguous effects on corporate tax revenue and FDI and challenge the joint mobilization of the two sources. Against this background, the paper discusses potential trade-offs faced by developing countries, when mobilizing corporate tax revenue and FDI jointly, and provides solutions how to address these trade-offs. A first trade-off exists between corporate tax incentives aimed at attracting FDI and the objective of increasing corporate tax revenue. A second trade-off results from the fact that policies that aim to protect corporate tax bases from erosion caused by tax avoidance and profit shifting may disincentivize FDI. The trade-offs can be addressed by reforms of the international tax system, while good national non-tax investment conditions are indispensable. The Inclusive Framework on BEPS has worked out reform proposals on a minimum corporate tax rate and on taxing the digital economy adequately which are currently discussed by its members. Many developing countries now actively participate in these discussions on future international tax rules. To avoid harmful trade-offs, countries need to consider the costs amd benefits of new tax rules and policies on both, their tax revenues and FDI attraction.
Keywords: 330; corporate tax revenue; FDI; financing for development; tax incentives; BEPS; multinational firms